Finding Inspiration (and Profit) in Maine’s Living Heritage: New Entrepreneurs Drawing upon the Past - Ettenger, Kreg (Maine Policy Review, 2020)
Maine has a rich heritage of traditional arts and industries that derive from its Indigenous and settler populations and the ways its people have used its natural resources and adapted to its diverse environments. This heritage continues today in a variety of forms, from economic activities like resource harvesting to artistic expressions such as music, dance, storytelling, and the visual arts. This essay looks at how traditional or folk activities, including foods, beverages, and other artisanal industries, continue to play an important role in Maine’s economic, social, and cultural landscape. Far from being quaint traditions maintained for cultural reasons, they are an important part of Maine’s new economy, helping to define its future through connections with its past.